Freudian Whimsy in William Shakespeare's King Lear (Jagannath University Journal of Arts, 2026)
William Shakespeare's King Lear is a play where one finds an apparently simple story of Lear, king of Britain, and his three daughters. However, it has gained immense popularity since its time of production. King Lear can be judged and criticized from various perspectives as researchers have applied plenty of literary theories and criticisms since the last century. From the gamut of literary theories King Lear can be analyzed from psychological perspectives. King Lear decides to divide his kingdom among his daughters for the cause of his old age as he claims. But the decision raises plenty of questions in the minds of thoughtful audiences, readers and researchers. Although Lear loves his younger daughter Cordelia very much, he disowns her. Very honest and noble Kent is also banished whimsically as he protests Lear's foolish thinking. From that juncture, this article ushers lights on King Lear from psychological perspectives especially referring to Freudian Whimsy and tries to find the answer to the research question of how does Freudian Whimsy intertwine in King Lear through Lear‟s activities and actions all through the drama. Maintaining a qualitative data analysis methodology, this article investigates the answer to the research question poses earlier. Hence, this article is a review article in which the text of King Lear, research articles, books assumes the role of secondary data. This article finds that Lear‟s actions from the beginning till end of the drama King Lear are an embodiment of Freudian Whimsy, i.e., the expressions of Freudian unconscious, id, ego and super-ego.Jagannath University Journal of Arts, v-5, i-01, 2025: p204-213